Maternal, pregnancy and fetal outcomes in de novo anti-glomerular basement membrane antibody disease in pregnancy: a systematic review - Thomson, Benjamin (Clin Kidney J, 2014)
BACKGROUND: Outside of pregnancy, anti-glomerular basement membrane (GBM) antibody disease is associated with significant morbidity and mortality. However, there is limited knowledge regarding de novo anti-GBM disease in pregnancy. METHODS: A systematic review was performed to identify maternal, pregnancy and fetal outcomes in de novo anti-GBM disease in pregnancy. Studies were selected from PubMed, EMBASE, Cochrane Library databases and conference proceedings, without language restriction. RESULTS: Data from eight patients were derived from seven case reports and one unpublished case. Most (6/8) patients presented after the first trimester. During pregnancy, acute kidney injury (5/8), anemia (5/8), hematuria (8/8) and proteinuria (8/8) were common. When hemodialysis was required antepartum (5/8), renal function recovery to independence of renal replacement was unlikely (2/5). While pulmonary involvement was common (5/8), no permanent damage was reported (0/8). The majority of cases ended in live births (6/8) although prematurity (6/6), intrauterine growth restriction (2/6), small for gestational age (4/6) and complications of prematurity (1/6) were common. When anti-GBM levels were tested in the living newborn, they were detectable (2/5), but no newborn renal or lung disease was reported (0/6). Complications in pregnancy included gestational diabetes (3/8), hyperemesis gravidarum (2/8) and preeclampsia (2/8). CONCLUSIONS: Live births can be achieved in de novo anti-GBM disease in pregnancy, but are commonly associated with adverse maternal, pregnancy and fetal outcomes. Only with awareness of common presentations, and management strategies can outcomes be optimized.